Preserving cognitive vitality: Value of cognitive rehabilitation in addressing cognitive deficits in the elderly - Furqan Ahmed Siddiqi; Muhammad Ehab Azim; Muhammad Furqan Hassan; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
The recent advancements in medical sciences has resulted in not only increasing life expectancy of the elderly but has also improved survival rate in elderly with neurological disorders including those with head trauma . This has resulted in an increasing number of persons with cognitive deficits. Cognitive functions such as executive functioning and memory play an important role in success of a rehabilitation programme and therefore can positively contribute to public health goals. Considering cognitive decline at present has no cure and pharmacological therapies have a limited role, efforts are usually made to delay the onset and progression of cognitive decline and improve quality of life. Literature suggests that active life style, regular exercise, actively performing activities of daily living can have a significant impact on cognitive skills. In addition different models of cognitive rehabilitation and approaches can be integrated into practice to improve cognitive reserve and cause neuroplastic changes to facilitate cognitive function by providing cognitive stimulus and training. Moreover with technological advancements, the computerized cognitive intervention field is growing. This usually integrates conventional cognitive intervention with digital smart devices to provide an engaging and cost effective alternate approach. This review aims to highlight the importance of cognitive rehabilitation and suggest a few evidence based approaches that may be considered by rehabilitation professionals to promote and improve cognitive rehabilitation in Pakistan. Keywords: Cognition, Cognitive Decline, Cognitive Rehabilitation, Elderly, Executive functions, Memory.